Polygraphy in hospitalized pediatric patients: A real-life practice. (Colombia Medica, 2024)
IntroductionEarly diagnosis of sleep disordered breathing allows early intervention, mitigating the multisystemic consequences. The test of choice for diagnosis and categorisation is polysomnography; its availability is limited, and alternatives such as polygraphy, which is more accessible and less expensive, have emerged.ObjectiveTo analyse the association between underlying pathologies and obstructive sleep apnoea-hypopnoea syndrome in children with suspected sleep-disordered breathing.MethodsRetrospective cross-sectional study. Polygraphs of children ≥1 year old hospitalised with suspected sleep-disordered breathing were included. Demographic, clinical, and polygraphic variables were collected.  Logistic regression analysis was performed to evaluate the presence of obstructive sleep apnoea-hypopnoea syndrome according to pathologies.ResultsOut of 1000 polygraphs, 407 were analysed. Mean age 8.2 years (4.1-12.2), 56% male. Primary diagnoses: neurological damage (19.4%), neuromuscular diseases (16%), upper airway obstruction (15.5%), and chronic pulmonary disease (15.5%). Altered polygraphy 56%; mild obstructive sleep apnea syndrome 63%, moderate 21%, and severe 16%, with obesity and neuromuscular diseases standing out. According to diagnosis, significant differences were found in age (p=0.001) and Apnea-hypopnea index (p=0.002).  Patients with Down syndrome had a 5.5 times higher risk of obstructive sleep apnoea-hypopnoea syndrome compared to patients with chronic pulmonary damage adjusted for age and Apnea-hypopnea index.ConclusionsThere was a high percentage of obstructive sleep apnoea-hypopnoea syndrome, especially in Obesity and neuromuscular diseases. Patients with Down's syndrome have a higher risk of obstructive sleep apnoea-hypopnoea syndrome than those with chronic pulmonary disease. Polygraphy is a potentially implementable tool in healthcare centres with similar characteristics and resources.